2008
DOI: 10.1111/j.1740-0929.2008.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in sacco dry matter degradability of residue and by‐products of palm fruit processing in the rumen of steers

Abstract: The nutritive value of residue (palm calyx leaves (PCL)) and by‐products (palm press fiber (PPF) and palm oil sludge (POS)) of palm fruit processing were studied through analysis of their chemical components and degradability of their dry matter (DM) in the rumen of steers. Chemical analysis showed that the materials have similar organic matter components (mean = 95.2%), while crude protein (CP, g/100 g) and metabolisable energy (ME, MJ/kg DM) were highest in POS (10.02 and 9.43), followed by PPF (7.02 and 8.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
4
5
0
Order By: Relevance
“…The a+b values of TMS 30572 and TMS 30555 are outstanding but ranked lower than potential degradability of highly degradable fodder tree species (Millettia thonningii, 'ito': PD=814 g/kg and Albizia lebbeck 'sivis': PD=940 g/kg) reported by Larbi et al (1996), Lablab (PD=737-847 g/kg) reported by Mupangwa et al (2003) as well as Ficus exasperata (PD=85.76%), Spondias mombin (PD=96.69%), Tectona grandis (PD=65.94%) and Terminalia catappa (PD=73.59%) reported by Ikhimioya et al (2005). The rate of degradation c that was best in Idileruwa and least in MS 6 was a reflection of the lignin contents of the incubated materials, and this corroborated observations made in previous studies (Sandoval-Castro et al 2005;Bamikole and Babayemi 2008). Better intake of Idileruwa than other varieties could be predicted in livestock based on their respective C-values, as this signals the potential ruminal load of the feed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The a+b values of TMS 30572 and TMS 30555 are outstanding but ranked lower than potential degradability of highly degradable fodder tree species (Millettia thonningii, 'ito': PD=814 g/kg and Albizia lebbeck 'sivis': PD=940 g/kg) reported by Larbi et al (1996), Lablab (PD=737-847 g/kg) reported by Mupangwa et al (2003) as well as Ficus exasperata (PD=85.76%), Spondias mombin (PD=96.69%), Tectona grandis (PD=65.94%) and Terminalia catappa (PD=73.59%) reported by Ikhimioya et al (2005). The rate of degradation c that was best in Idileruwa and least in MS 6 was a reflection of the lignin contents of the incubated materials, and this corroborated observations made in previous studies (Sandoval-Castro et al 2005;Bamikole and Babayemi 2008). Better intake of Idileruwa than other varieties could be predicted in livestock based on their respective C-values, as this signals the potential ruminal load of the feed.…”
Section: Discussionsupporting
confidence: 83%
“…The availability of these grasses is also seasonal. Ruminant livestock raised in this region, therefore, tend to reflect the cyclical variation in the quantity and quality of these available forages (Bamikole and Babayemi 2008). Ruminant animals, because they have pregastric fermentative digestion of feed, generally do not compete with human beings for vital quality feed resources.…”
Section: Introductionmentioning
confidence: 99%
“…Ether extract (EE) concentration was high in both the PPF and POS but low in PCL in all the three varieties. The high content of EE in PPF and POS is consistent with our earlier observation (Bamikole & Babayemi 2008) in Nigeria and that of Obese et al. (2001) in Ghana.…”
Section: Discussionsupporting
confidence: 93%
“…All the varieties had higher concentrations of Cu and Fe in their POS, PPF and PCL and this is consistent with observations made in our earlier study (Bamikole & Babayemi 2008). Mineral composition of by‐products from cocoa published by Aregheore (2002) had higher content of Cu but lower content of Fe than what we have obtained in the materials in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation